European election: New EU Parliament, new EU Commission - new impetus for Workers' Voice? - Martin Feldmann; Maxi Leuchters; Oliver Emons; Norbert Kluge; Sebastian Sick; Marion Weckes (Hans-Böckler-Stiftung, Institut für Mitbestimmung und Unternehmensführung (I.M.U.), 2019)
In the wake of the European elections on 25 May 2019 we will have a new European Parliament and European Commission. Little progress was made on collective rights during the last legislative period. All the more reason, then, for the next European Commission and European Parliament to prioritise strengthening workers' participation. The report points to specific areas in which regulations must be supplemented and amended in order to boost workers' participation and workers' rights.
Keywords: 330